Electronically tunable voltage-mode universal filter with three-input single-output - Kumngern, Montree; Dejhan, Kobchai (My University, 2010)
A new electronically tunable voltage-mode universal filter with three-input single-output using six simple CMOS operational transconductance amplifiers and two capacitors is proposed. The proposed filter provides lowpass, bandpass, highpass, bandstop and allpass voltage responses. Also, the parameters ωo and Q can be set orthogonally by adjusting the circuit components. The performances of the proposed circuit are simulated with PSPICE to confirm the presented theory. ©2010 IEEE.
Keywords: OTA; Universal filter; Voltage-mode